1983
DOI: 10.1021/bi00270a023
|View full text |Cite
|
Sign up to set email alerts
|

A triglobular model for the polypeptide chain of aspartokinase I-homoserine dehydrogenase I of Escherichia coli

Abstract: Limited proteolysis of aspartokinase I-homoserine dehydrogenase I from Escherichia coli by type VI protease from Streptomyces griseus yields five proteolytic fragments, three of which are dimeric, the other two being monomeric. One of the monomeric fragments (27 kilodaltons) exhibits residual aspartokinase activity, while the second one (33 kilodaltons) possesses residual homoserine dehydrogenase activity. The smallest of the dimeric species (2 X 25 kilodaltons) is inactive; the two other dimers exhibit either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…The native molecular weight of the normal AKI-HDI protein was 280,000 to 370,000. This was consistent with the hypothesis that it is a tetramer like the E. coli enzyme (10,12). The truncated AKI-HDI molecules containing the N-terminal 462 and 468 amino acid residues were probably dimeric, and the shorter molecules were probably monomeric.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The native molecular weight of the normal AKI-HDI protein was 280,000 to 370,000. This was consistent with the hypothesis that it is a tetramer like the E. coli enzyme (10,12). The truncated AKI-HDI molecules containing the N-terminal 462 and 468 amino acid residues were probably dimeric, and the shorter molecules were probably monomeric.…”
Section: Resultssupporting
confidence: 89%
“…The E. coli AKI-HDI enzyme is a large tetrameric protein (10,19). Proteolytic digestion has shown that the AKI and HDI activities are carried by the N-terminal and C-terminal moieties, respectively, and that multimer formation depends on the central region (11,12).Threonine synthesis in Serratia marcescens has been studied extensively (22,23). Both AKI and HDI activities are subject to feedback inhibition by threonine, and expression of the thr operon is multivalently repressed by threonine and isoleucine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…y-glutamyl kinase and responsible for the aspartokinase activity (18), the hydrophobic interaction between this region and the central region is probably involved in the allosteric regulation of AKI. A triglobular model for the polypeptide chain of the intact AKI-HDI protein has been proposed (6). These hydrophobic interactions among the AKI, HDI, and central domains may be possible factors in the allosteric regulation of the AKI-HDI protein.…”
mentioning
confidence: 99%
“…On the other hand, limited proteolysis of native AK I/ HDI I under very mild conditions has yielded a variety of proteolytic fragments with principally a homodimeric HDH fragment carrying only the dehydrogenase activity [15,16] and a hybrid fragment composed of the association of a complete subunit with a proteolysed polypeptide [17]. Previous analysis of the kinetics of this proteolytic reaction have led to the hypothesis that dimers of AK I/HDH I were the true substrates of the protease and that the enzyme in its tetrameric state was rather resistant to proteolytic degradation [9, 181. In this paper we describe conditions for the reversible dissociation of AK I/HDH I into dimers and we use their selective sensitivity to limited proteolysis to demonstrate that these dimers reassociate very rapidly into tetramers under the conditions of assay.…”
mentioning
confidence: 99%